Memory and critique: Essays on the history of education and school in Spain and Germany - Roith, Christian (Editorial Universidad de Almería, 2015)
The present volume collects the updated versions of several contributions already published elsewhere and some new chapters on the history of education in Spain and Germany which have been brought together in this form for the benefit of those attending English-language classes on the topic aimed at international as well as Spanish students. The individual articles function as case studies of different fields in the history of education. They are characterised not only by their difference in focus, but also in the methods and sources they include, providing an insight into the breadth and variety of the field. It is particularly noteworthy that the comparative orientation of several articles moves beyond a national perspective of history, demonstrating concrete examples of the transnational interconnectedness of producing and circulating educational knowledge.